DAKWAH KEPADA PEREMPUAN DAN ANAK-ANAK Perspektif Hadis Rasulullullah Saw. - Rabiatul Aslamiah (UIN Antasari Banjarmasin, 2020)
The preaching of Islam is actually for all mankind. The Messenger of Allah (may peace be upon him) delivered his preaching not only to men but also to women and children. He provided a special time to preach to women. He also preaches and gives guidance and advice to children.